IRRIGATION INTERVALS IN THE PRODUCTION OF ORNAMENTAL PINEAPPLE IN POTS - Bomfim, Guilheme Vieira do (2020)
Information on irrigation management is essential in a production system for the commercial cultivation of ornamental pineapple in pots. As such, this work evaluated the effects of irrigation interval on the growth and production of the crop in pots. The experiment was carried out from 16/07/2015 to 21/05/2016 in a greenhouse located in Fortaleza, in the state of Ceará, Brazil. The experimental design was completely randomised, with five treatments, four replications and four plants per plot. The treatments consisted of irrigation intervals of 2, 4, 6, 8 and 10 days. The plants were grown in one-litre pots, fertilised with slow release fertiliser and subjected to supplementary drip irrigation. The following variables were analysed at the end of the cycle (402 days): number of leaves; length and width of the 'D' leaf; diameter of the rosette; plant height; rate of flowering; length and diameter of the peduncle, syncarp and crown; crown to syncarp ratio; and percentage of commercial plants. The irrigation interval influenced the number of leaves, length of the 'D' leaf, diameter of the rosette, plant height, rate of flowering and percentage of commercial plants. Irrigating every two days resulted in water savings, increased leaf growth and a high rate of flowering, and the greatest percentage of commercial plants. Irrigating at intervals of between four and 10 days, increased water wastage, and reduced leaf growth, the rate of flowering and the percentage of commercial plants. The shortest irrigation interval is therefore the most recommended for cultivation in pots.